The Equation of Motion Phonon Method and its application to neutron rich odd nuclei. (May 2020) - De Gregorio, G.; Knapp, F.; Lo Iudice, N.; Veselý, P.
Abstract: We report on the extension to odd nuclei of a microscopic multiphonon approach known as equation of motion phonon method and its application to the odd neighbors of the neutron rich 22 O. A calculation using the chiral potential NNLO opt and encompassing up to two phonon basis states provides a description of the spectroscopic properties which is good quantitatively for 23 O and qualitatively for 21 O and 21 N. Serious discrepancies between theory and experiments occur in 23 F. A possible recipe for curing them is under investigation.